Medication Reconciliation: An Educational Module - Paula E. Lester; Sukhminder Sahansra; Mark Shen; Maria Becker; Shahidul Islam (Association of American Medical Colleges, 2019)
Introduction Patients often transition between health care settings, such as office to hospital, hospital to nursing facility, or hospital to home. When a patient is admitted, it is imperative that clinicians review prior medication lists along with new orders to reconcile any discrepancies. This process should occur in a standardized manner to reduce medication errors leading to adverse events and patient harm. Methods We developed this program as an instructional method via PowerPoint to teach the importance of accurate medication reconciliation. We implemented the program in multiple grand rounds settings with students, trainees, and attending physicians in internal medicine and surgery. Approximately 150 learners attended the sessions. We assessed learners with pre/post self-efficacy assessment (74 completed precourse surveys, 39 completed posttest surveys, and 49 participated in the audience response during the course) and multiple-choice knowledge questions. Results The results of the postcourse knowledge assessment demonstrated improvement in every question we tested, with two of the improvements reaching statistical significance. We found that 30% of attendees were not at all confident or only somewhat confident in conducting an appropriate medication reconciliation on admission to the hospital. Additionally, 82% of respondents reported that the presentation was likely or extremely likely to improve their medication reconciliation efforts. Discussion Our educational program was successful in improving learners' knowledge in every question we tested; however, only two of the improvements were statistically significant. Our program is an organized and effective tool for teaching effective and reliable medication reconciliation.